Neuromyths in Chinese Classrooms: Evidence From Headmasters in an Underdeveloped Region of China - Zhang, Ronghua; Jiang, Yanfei; Dang, Baobao; Zhou, Aibao (Frontiers in Education, 2019)
Neuromyths are misinterpretations of neuroscientific knowledge that may negatively affect the development of science-based education. They arise from complex scientific advances that are often communicated in a simplified form by the media and consumed by the untrained public, including education professionals, in a variety of cultural and social contexts. To better understand such variations, the present research used a questionnaire to survey the belief in neuromyths among headmasters in Gansu province in northwestern China. In all, 253 headmasters of the elemental and middle school participated in the survey, the results showed that headmasters in Gansu province were interested in neuroscience and that they commonly believed neuromyths. The most widespread neuromyths were those about learning styles, rich environments for pre-school children, and exercise to improve brain function. The educators’ personal backgrounds, such as level of education and school type, may be predictive of their belief in neuromyths. Our results indicated that headmasters must be alert in attempting to apply neuroscience laboratory results to classroom teaching.